(untitled) (Gestionar: revista de empresa y gobierno, 2022)
The purpose of this research was to evaluate the Destination Management Organization (DMO) of Lake Titicaca destination, province of Puno - Peru, by measuring the effectiveness of its tourism planning instruments and seeking to establish a relationship between said effectiveness and its destination management capacity. For this purpose, a mixed approach methodology was chosen, with a non-experimental, descriptive and cross-sectional correlational design. Based on an intentional non-probabilistic sampling, a structured survey with a Likert scale was applied to the public managers and stakeholders involved in the aforementioned tourist space. The results made it possible to show that tourism planning instruments are not effective, with large gaps and inconsistencies between them. In addition, there is a direct relationship between the effectiveness of these instruments and the management capacity of the competent entity of the destination, limiting the opportunities for development and competitiveness of its own destination. It is possible to affirm that for a strengthening of management, a leading entity is required, representative and consistent with its planned actions and measures.